A Systematic Literature Review of the Context of the Sharing Economy and CSR in 2017-2021 - Tetřevová, Liběna; Kopřiva, Jan; Kocúriková, Alexandra (Sciendo, 2023)
The sharing of idle assets, on which the sharing economy model is based, is associated with positive economic, environmental, and social effects, the creation of which is the basis of the concept of corporate social responsibility (CSR). It would therefore seem expedient to examine the context of these phenomena, which have recently been gaining in importance, although they still remain outside mainstream research. So far, there is no study which comprehensively characterises the current state of knowledge of the context of the sharing economy and CSR, identifies research gaps, and postulates directions for future research in this area. This article addresses this gap by utilising a standalone literature review approach. An analysis of 20 publications, published on this topic in 2017-2021 in journals registered in the Web of Science and Scopus databases, was carried out. Four main research clusters were identified, these being (1) The sharing economy as a tool of the CSR concept; (2) The joint contribution of the sharing economy model and the concept of CSR towards reduction of overconsumption and wastage; (3) The importance of CSR communication for sharing economy platforms; and (4) The antagonistic relationship between the sharing economy model and the concept of CSR. The performed analysis shows the fragmented nature of existing research, but also the progressive nature of this area of research. At the same time, useful avenues for future research are postulated. This should focus on multiple lines of inquiry, including the possibility of incorporating different forms of B2B sharing into the concept of CSR, assessing the benefits, limitations, and risks of linking these two concepts, as well as exploring the synergies between the sharing economy model and the concept of CSR from the point of view of different industries, sharing segments, or regions.
Systematická literární rešerše kontextu sdílené ekonomika a CSR v letech 2017-2021
Keywords: collaborative consumption; collaborative economy; corporate social responsibility; CSR; sharing economy; systematic review; kolaborativní spotřeba; kolaborativní ekonomika; společenská odpovědnost firem; CSR; sdílená ekonomika; systematická rešerše